Therapeutic effects of a novel synthetic α-secretase - Kim, Sung Bin; Mun, Bo-Ram; Kim, Sung Yoon; Elangovan, Muthukumar; Park, Euy Jun; Choi, Won-Seok; Park, Woo Jin (Frontiers in Aging Neuroscience, 2024)
Excessive accumulation of amyloid-β (Aβ) has been associated with the pathogenesis of Alzheimer’s disease (AD). Clinical studies have further proven that elimination of Aβ can be a viable therapeutic option. In the current study, we conceptualized a fusion membrane protein, referred to as synthetic α-secretase (SAS), that can cleave amyloid precursor protein (APP) and Aβ specifically at the α-site. In mammalian cells, SAS indeed cleaved APP and Aβ at the α-site. Overexpression of SAS in the hippocampus was achieved by direct injection of recombinant adeno-associated virus serotype 9 (AAV9) that expresses SAS (AAV9-SAS) into the bilateral ventricles of mouse brains. SAS enhanced the non-amyloidogenic processing of APP, thus reducing the levels of soluble Aβ and plaques in the 5xFAD mice. In addition, SAS significantly attenuated the cognitive deficits in 5xFAD mice, as demonstrated by novel object recognition and Morris water maze tests. Unlike other Aβ-cleaving proteases, SAS has highly strict substrate specificity. We propose that SAS can be an efficient modality to eliminate excessive Aβ from diseased brains.